RESPONSE OF EXOTIC VEGETABLES TO PLANT SPACING, FERTILIZATION, AND INSECT PEST MANAGEMENT UNDER SUBTROPICAL REGION OF WESTERN HIMALAYAS OF HIMACHAL PRADESH - RENU KAPOOR; DHARMINDER KUMAR; CHANDEL VGS; ANIL KUMAR; ANURAG SHARMA; RAJESH KALER; VIPAN GULERIA (Innovare Journal of Agricultural Sciences, 2024)
Objective: The study was conducted with the objective to study the effect of different plant spacing and fertilizer treatments on the yield and growth parameters of exotic vegetables. Methods: The study was carried out at the experimental farm of Regional Horticultural Research and Training Station Jachh (32° 16’ N latitude and 75°51’ E longitude, 440 m above mean sea level) during the year 2021–22. The experiment was laid out in a factorial randomized complete block design with three replications. The treatments were comprised of three levels of fertilizers (120, 100, 75% RDF) and two levels of spacing. Results: The observations revealed significant variations in the fresh yield of Kale, Parsley, and Celery in response to different fertilizer doses and plant spacing. Specifically, the fresh yield of Kale, Parsley, and Celery showed significant improvements with higher levels of fertilization (F1) and narrow plant spacing (S2). In addition, the number of leaves per plant increased with higher fertilizer doses but did not vary significantly across different spacing levels in all three crops. While the leaf length and width of Kale were not significant, the leaf length of Parsley and Celery varied significantly with increasing fertilizer doses. Furthermore, among the three crops studied, Kale was observed to be infested by aphids, particularly Brevicoryne brassicae, during the crop period. The application of imidacloprid (0.5 ml/L) and chlorantraniliprole (0.4 ml/L) demonstrated effective management of this pest, providing better results for pest control. Conclusion: Fresh yield of kale, parsley, and celery increased under high level of fertilization and narrow spacing as well. Moreover, imidacloprid and chlorantraniliprole can be utilized for the management of cabbage aphids in Kale crop.